Ethanol conversion in glow and barrier discharges - Levko, D.S.; Tsymbaluk, A.N.; Kolgan, V.V. (Вопросы атомной науки и техники, 2014)
The efficiency of ethanol conversion in glow and barrier discharges is analyzed. It is found that for a given power the ethanol conversion is more efficient in glow discharge. This is caused by the principal difference in the way of generation of active atoms and radicals in both types of discharges. In addition, the main channels leading to the generation and quenching of H₂ and CO are studied. The method to increase the efficiency is proposed.